The Level of Damage Caused by the Sweetpotato Weevil (Cylas formicarius) Attack on Purple Sweet Potato (Ipomoea batatas) Under Two Mulch Treatments - Syafira, Al Madiah; Supeno, Bambang; Muthahanas, Irwan (Jurnal Biologi Tropis, 2026)
The sweetpotato weevil (Cylas spp.) is one of the major pests of sweet potato that can reduce both the quality and quantity of yield, as it attacks not only the tubers but also acts as a stem borer. This study aimed to determine the effect of mulch application on the attack intensity of Cylas spp. on purple-fleshed sweet potato (Ipomoea batatas), to examine the distribution pattern of pest populations on tubers and stems, and to analyze the relationship between pest population and the resulting attack intensity. The study was conducted using a Randomized Block Design (RBD) with three treatments, namely control (F0), plastic mulch (F1), and straw mulch (F2), each replicated nine times, resulting in 27 experimental units. The results showed that the application of different types of mulch did not significantly affect the attack intensity of the sweetpotato weevil. Nevertheless, the straw mulch treatment produced the lowest attack intensity at 4.07%, followed by the control at 4.99%, and plastic mulch at 5.13%, with all treatments classified under the mild attack category (intensity below 10%). Cylas populations were found attacking both tubers and stems, with the highest population recorded in the control treatment (10.33 individuals on tubers and 5.00 individuals on stems), followed by straw mulch (4.33 and 2.56 individuals), and the lowest in plastic mulch (3.67 and 0.78 individuals). Pest populations on tubers were consistently higher than on stems, indicating that tubers are the primary target of adult Cylas spp. attack. Correlation analysis revealed a positive relationship between pest population and attack intensity, although classified as weak, with a correlation coefficient (R) of 0.314, indicating that an increase in pest population tends to be followed by an increase in attack intensity, although not consistently strong.